L'impact des événements d'innovation ouverte - Armellini, Fabiano; Veilleux, Sophie (2021)
L’objectif de ce rapport (rédigé notamment par Fabiano Armellini et Sophie Veilleux) est de présenter les meilleures pratiques, les indicateurs de succès ainsi que les mesures d’impact des événements d’innovation ouverte sur leurs écosystèmes respectifs. Ainsi, chaque acteur est en mesure d’optimiser sa participation afin d’en retirer un maximum de bénéfices et d’en faire profiter son écosystème. Ce rapport offre aussi plusieurs recommandations.
Keywords: Innovation ouverte; Meilleures pratiques; Mesure d'impact

How to measure the impact of social innovation initiatives? - Cunha, Jorge; Benneworth, Paul (International Review on Public and Nonprofit Marketing, 2020)
Academic literature about the idea of social innovation grew sharply over the last decade, with researchers trying to define its concept and presenting several examples of successful social innovations. However, to support the development of social innovation initiatives is important to have a conceptual framework that allows evaluating its true impact. The purpose of this paper is to identify the boundary conditions for an effective set of social innovation indicators, which will help to have a more informed decision-making process. The main conclusion is that the impact of social innovations can be conceived as a set of results that manifests itself through different time periods, at different spatial scales, and must take into account the value experienced by all stakeholders involved. Thus, since a positive social innovation outcome depends on diverse factors and conditions, being most often context-dependent, it means that rather than imposing a specific set of indicators, based on a ‘one-size-fits-all’ approach a measuring process procedure should be adopted to assess the impact of social innovations.
Keywords: Mesure d'impact; Université; Version libre-accès Open Repository

Is measuring social innovation a mission impossible? - Mihci, Hakan (Innovation, 2020)
The main aim of the paper is to question the viability of measuring social innovation with the current state of knowledge on the one hand, and to make suggestions for better measurement of it on the other. To reach this aim, the literature on the traditional measures of technological innovation and the previous attempts of measuring social innovation is surveyed. Despite relatively narrow scope of the literature mainly originated from the very recent and pioneer experiments, one may argue that the first findings do not present a promising picture for future studies. Therefore, existing trials to measure social innovation have to be critically screened to ascertain problematic areas, and hence, to provide plausible solutions. The problems with social innovation metrics are not only limited with obtaining concrete and trustworthy results, but also extended to statistical, methodological and even conceptual spheres.
Keywords: Indicateur; Innovation; Innovation sociale; Innovation technologique; Mesure d'impact; Réservé UdeM

The Impact of Societal and Social Innovation: a Case-Based Approach - Lin, Carol Yeh-Yun; Chen, Jeffrey (Springer Singapore, 2016)
Keywords: Asie; Changement systémique; Entrepreneuriat social; Europe; Innovation; Innovation sociale; Innovation sociétale; Mesure d'impact; Parties prenantes; Processus d'innovation; Réservé UdeM; Étude de cas